PENGARUH KINERJA LINGKUNGAN, BIAYA LINGKUNGAN DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dida Nurfadila; Rohma Septiawati; Ihsan Nasihin (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2025)
This study examines the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023 in relation to environmental performance, environmental costs, and company size. The phenomenon shows how the financial performance of various companies in the consumer goods subsector varies, with some companies experiencing instability and others experiencing growth. Although environmental management can improve an organization's reputation and investor confidence, businesses usually consider it a burden. The purpose of this research is to study how environmental performance, environmental costs, and company size affect financial performance. This study uses a quantitative approach with secondary data as the source obtained from the annual report and sustainable reporting from the official IDX website in accordance with the variable indicators. The population was 72 companies with a sample of 21 companies with sample selection using purposive sampling, then analyzed using SmartPLS4 with several stages, namely, outher model outher loadings, construct reliability and validity tests, and discriminant validity then evaluating the inner model r-square and hypothesis. The study findings show that financial success is negatively affected by environmental performance, indicating that the short-term benefits of sustainability have not been realized. On the other hand, financial performance is positively and significantly affected by environmental costs, which suggests that investments in environmental management can improve a company's operational effectiveness and reputation. Financial performance is also positively affected by firm size, which suggests that larger businesses are better equipped to meet shareholder expectations. These findings support stakeholder theory, which emphasizes the balance between business interests and environmental concerns in improving corporate financial performance.